2021
DOI: 10.1186/s41118-021-00130-w
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment for COVID-19 transmission at household level in sub-Saharan Africa: evidence from DHS

Abstract: Household habitat conditions matter for diseases transmission and control, especially in the case of the novel coronavirus (COVID-19). These conditions include availability and adequacy of sanitation facilities, and number of persons per room. Despite this, little attention is being paid to these conditions as a pathway to understanding the transmission and prevention of COVID-19, especially in Africa, where household habitat conditions are largely suboptimal. This study assesses household sanitation and isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
2
4
1
Order By: Relevance
“…These results may be due to increased intergenerational mixing at the household level, as prior research in Africa has shown that households sharing space with persons aged 60+ years may have increased transmission risk. 46 We also found lower seroprevalence was associated with rural geographical areas compared with urban areas, in line with other hypotheses and modelling associating rural areas with a potentially lower spread of infection due to decreased population density. 51 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results may be due to increased intergenerational mixing at the household level, as prior research in Africa has shown that households sharing space with persons aged 60+ years may have increased transmission risk. 46 We also found lower seroprevalence was associated with rural geographical areas compared with urban areas, in line with other hypotheses and modelling associating rural areas with a potentially lower spread of infection due to decreased population density. 51 …”
Section: Discussionsupporting
confidence: 91%
“…The exact reasons for this heterogeneity remain unknown but could be related to mitigation strategy, health infrastructure and the effectiveness of PHSM implementation. The capacity to isolate has been shown to vary greatly in Africa, 46 and challenges have been reported with social distancing in the Western and Middle subregions, especially in high density areas. 47 48 This is also consistent with findings by Chisale et al , 8 who observed higher seroprevalence in studies conducted in Central Africa compared with other regions.…”
Section: Discussionmentioning
confidence: 99%
“…[48] In contrast to our global analysis,[9] we did not find lower seroprevalence in adults 60+ years compared to adults 20-29 years. These results may be due to increased intergenerational mixing at the household level, as prior research in Africa has shown that households sharing space with persons ages 60+ may have increased transmission risk [44]. We also found lower seroprevalence was associated with rural geographical areas compared to urban areas, in line with other hypotheses and modelling associating rural areas with a potentially lower spread of infection due to decreased population density.…”
Section: Discussionsupporting
confidence: 89%
“…The exact reasons for this heterogeneity remain unknown but could be related to mitigation strategy, health infrastructure, and the effectiveness of PHSM implementation. The capacity to isolate has been shown to vary greatly in Africa, [44] and challenges have been reported with social distancing in the Western and Middle sub-regions, especially in high density areas. [45,46] This is also consistent with findings by Chisale et al .…”
Section: Discussionmentioning
confidence: 99%
“…Other notable factors implicated in the sustained transmission include access to sanitation facilities, age and underlying comorbidities. 1,2 While the literature is replete with evidence to show that attitude and behaviour, encapsulated in health beliefs, matter for the spread of infectious diseases, studies have further confirmed same to be valid with Covid-19. [3][4][5][6][7][8] Individuals, according to the health belief model (HBM), prevent or expose themselves from/to diseases based on their perception of their susceptibility, the severity of the disease, benefits accruable from engaging in protective behaviour, barriers to the protective behaviour, factors that could lead them to adopting the protective behaviour, and their perceived efficacy of the protective action.…”
Section: Introductionmentioning
confidence: 99%